2015
DOI: 10.1088/1742-6596/654/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic representation of the Klein-Gordon-Einstein equations in the weak field limit

Abstract: Using a generalization of the Madelung transformation, we derive the hydrodynamic representation of the Klein-Gordon-Einstein equations in the weak field limit. We consider a complex self-interacting scalar field with an arbitrary potential of the form V (|ϕ| 2 ). We compare the results with simplified models in which the gravitational potential is introduced by hand in the Klein-Gordon equation, and assumed to satisfy a (generalized) Poisson equation. Nonrelativistic hydrodynamic equations based on the Schröd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(60 citation statements)
references
References 40 publications
0
60
0
Order By: Relevance
“…The Madelung equations resemble the continuity and Euler equations of classical fluid dynamics, with the addition of a 'quantum pressure' term accounting for resistance against gravitational collapse. The Madelung formalism is discussed in detail in [43,[46][47][48]. Because this hydrodynamical formulation defines the fluid velocity as the gradient of the phase of the field ψ, problems arise when ψ = 0, where the phase is not well defined.…”
Section: Tidal Disruption Of Solitons Orbiting a Central Potentialmentioning
confidence: 99%
“…The Madelung equations resemble the continuity and Euler equations of classical fluid dynamics, with the addition of a 'quantum pressure' term accounting for resistance against gravitational collapse. The Madelung formalism is discussed in detail in [43,[46][47][48]. Because this hydrodynamical formulation defines the fluid velocity as the gradient of the phase of the field ψ, problems arise when ψ = 0, where the phase is not well defined.…”
Section: Tidal Disruption Of Solitons Orbiting a Central Potentialmentioning
confidence: 99%
“…1 In a recent work, 2,3 we have developed a hydrodynamic representation of the Klein-Gordon-Einstein (KGE) equations in the weak field limit. In these proceedings, for conciseness, we present the nonrelativistic limit of these fluid equations that was obtained in our earlier works, 4,5 and we study the growth of perturbations in the linear regime.…”
Section: Introductionmentioning
confidence: 99%
“…In the relativistic case, de Broglie [72][73][74] in his so-called pilot wave theory, showed that the KG equations are equivalent to hydrodynamic equations including a covariant quantum potential. This approach has been generalized to the Klein-Gordon-Poisson (KGP) and KGE equations in the context of DM halos by [75][76][77][78][79]. 2 In this hydrodynamic representation, DM halos result from the balance between the gravitational attraction and the quantum pressure arising from the Heisenberg uncertainty principle or from the self-interaction of the bosons.…”
mentioning
confidence: 99%